ANALYSIS OF DIGITAL EDUCATION CONSTRAINTS DURING THE COVID-19 PANDEMIC IN G-20 MEMBER COUNTRIES - Rostamaji Korniawan (Wacana Publik, 2022)
Abstract The discussion of the constraints of digital education is the theme of discussion in this study. Digital education is being discussed considering the transformation of education is carried out by all countries, including countries members of the G20. However, in its implementation, digital education faces several obstacles. Therefore, this study aims to explain the obstacles several countries face in implementing digital education in their country. Five countries are observed where the five countries are countries that are members of the G20 membership, namely Indonesia, India, South Africa, Poland, and Hungary. The study uses a literature approach with an observation period in 2020 during the Covid-19 pandemic. Based on the analysis, the results show that the five countries face a shortage of facilities and means to support digital education. In addition, the unpreparedness of users of digital education system services is also another obstacle. These obstacles are the main obstacles faced. For this reason, the discussion of the cooperation forum for the G20 countries consistently seeks to encourage better economies of scale so that an inclusive economy can be achieved in all G20 member countries. The success of achieving an inclusive economy can build a better digital education infrastructure in the future.